2017
DOI: 10.1016/j.cplett.2016.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence dynamics in singlet fission chromophore liquid melts

Abstract: The effect of high temperature melting on the photophysics of three prototypical singlet fission molecules is investigated. Time-resolved photoluminescence is used to look at the melt phase of the molecules tetracene, diphenylhexatriene and rubrene. Chemical decomposition of tetracene precluded any detailed measurements on this molecule. In the diphenylhexatriene melt, a rapid singlet state nonradiative relaxation process outcompetes singlet fission. In the rubrene melt, singlet fission occurs at a rate simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…13 For rubrene-deposited films, thermally activated SF was found in the temperature range 50−300 K, and the activation energy was estimated to be 110 cm −1 . 14 For powder samples, it has been observed that the fluorescence decay profiles do not change with temperature in the temperature range 566−856 K. 15 This result clearly shows that a reliable fluorescence study with rubrene crystals will require that the quality of the crystals be carefully taken into account. In fact, fluorescence spectra of single crystals are known to be sensitive to the procedure used to grow the crystal.…”
Section: Introductionmentioning
confidence: 95%
“…13 For rubrene-deposited films, thermally activated SF was found in the temperature range 50−300 K, and the activation energy was estimated to be 110 cm −1 . 14 For powder samples, it has been observed that the fluorescence decay profiles do not change with temperature in the temperature range 566−856 K. 15 This result clearly shows that a reliable fluorescence study with rubrene crystals will require that the quality of the crystals be carefully taken into account. In fact, fluorescence spectra of single crystals are known to be sensitive to the procedure used to grow the crystal.…”
Section: Introductionmentioning
confidence: 95%
“…This is in contrast to the emission behavior of the thin-film sample, which displays the decay of mainly excitonic emission with a very weak contribution of long-lived low-energy emission at 500–650 nm. Thus, even though both NA and TF undergo enhanced deactivation of the excitonic state, decay channels in two samples are significantly different, presumably due to sample morphology and crystallinity …”
Section: Resultsmentioning
confidence: 99%
“…Thus, even though both NA and TF undergo enhanced deactivation of the excitonic state, decay channels in two samples are significantly different, presumably due to sample morphology and crystallinity. 50 To unravel the nonradiative decay mechanism of singlet excitons in NA and TF samples of TIPSAn, ultrafast transient spectral dynamics of TIPSAn NA and TF were compared with those of the monomer. TA spectra of TIPSAn in THF solution are similar to those of the previously reported similar anthracene derivative BPEA.…”
Section: Resultsmentioning
confidence: 99%
“…340 °C). 64 If SF observed in such a high-temperature melt state can be realized in a fluid state at room temperature (r.t.), it would be an innovative material with no mechanical brittleness and excellent processability, taking advantage of the properties of fluids. SF in molecular fluids is thus expected to attract great attention in the research areas such as photorelated catalysis and electronics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The only example of SF with fluid molecular systems so far has been reported in the melt phases of pristine rubrene (at ca. 340 °C) . If SF observed in such a high-temperature melt state can be realized in a fluid state at room temperature (r.t.), it would be an innovative material with no mechanical brittleness and excellent processability, taking advantage of the properties of fluids.…”
Section: Introductionmentioning
confidence: 99%